2020
DOI: 10.31557/apjcc.2020.5.2.119-123
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 18F-FDG-PET/CT Scan in the Management of Multiple Myeloma

Abstract: Bone lesion is a myeloma-defining event which is reported in 80% of multiple myeloma patients. Imaging of bone is essential in the evaluation of pattern and extent of bone involvement. Recently, whole body X ray (WBXR) has been replaced by more accurate imaging such as whole bode MRI and FDG-PET/CT scan. This review article provides the advantages and role of PET/CT scan in the diagnosis and management of multiple myeloma patients. Generally, PET/CT in diagnosis of bone involvement of newly diagnosed myeloma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Multiple myeloma is a plasma cell dyscrasia characterized by multi-organ involvement including osteoclastic activation leading to osteolytic bony lesions observed in 80% of MM patients. 10 It is one of the most frequent presentations therefore prompt evaluation by imaging techniques is the corner stone of diagnosis of bone involvement in MM patients. In terms of diagnosis, skeletal survey is less sensitive than PET/CT although it was used to be the gold standard modality for evaluation of bony lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma is a plasma cell dyscrasia characterized by multi-organ involvement including osteoclastic activation leading to osteolytic bony lesions observed in 80% of MM patients. 10 It is one of the most frequent presentations therefore prompt evaluation by imaging techniques is the corner stone of diagnosis of bone involvement in MM patients. In terms of diagnosis, skeletal survey is less sensitive than PET/CT although it was used to be the gold standard modality for evaluation of bony lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant advantage of 18 F-FDG PET/CT is its ability to accurately assess the severity of the disease and to distinguish between active metabolic lesions and inactive lesions [ 39 41 ]. PET/CT reveals multiple osteolytic lesions throughout the skeleton ( Figure 3 ) (skull, ribs, upper limbs, femurs, pelvis and spine), with a short image acquisition time with 3-D tomographs, important in patients with fractures or bone pain [ 42 , 43 ].…”
Section: Positron Emission Tomography With Computed Tomography 18f-de...mentioning
confidence: 99%
“…A systematic review of 18 studies comparing 18 F-FDG PET/CT with WBXR, or MRI, confirmed that MRI is the gold standard technique for assessing diffuse involvement of the bone marrow, while 18 F-FDG PET/CT is more sensitive than WBXR for bone damage detection [ 39 , 50 ].…”
Section: Positron Emission Tomography With Computed Tomography 18f-de...mentioning
confidence: 99%